1999
DOI: 10.1094/phyto.1999.89.2.113
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the Development of Host Resistance in Corn to Aflatoxin Contamination by Aspergillus flavus

Abstract: Aflatoxins are toxic, highly carcinogenic secondary metabolites of Aspergillus flavus and A. parasiticus, which when produced during fungal infection of a susceptible crop in the field or after harvest contaminate food and feed and threaten human and animal health. Although there are several management strategies that may reduce aflatoxin contamination of corn, the preeminent strategy for elimination of aflatoxin is to develop preharvest host resistance to aflatoxin accumulation. This strategy has gained even … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
96
0
3

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(99 citation statements)
references
References 27 publications
0
96
0
3
Order By: Relevance
“…(reviewed in Brown et al, 1999). The results of these studies indicate the presence of two levels of resistance: at the pericarp and at the subpericarp level.…”
Section: Development Of Aflatoxin-resistance Screening Toolsmentioning
confidence: 99%
See 2 more Smart Citations
“…(reviewed in Brown et al, 1999). The results of these studies indicate the presence of two levels of resistance: at the pericarp and at the subpericarp level.…”
Section: Development Of Aflatoxin-resistance Screening Toolsmentioning
confidence: 99%
“…With corn, the strategy of enhancing host resistance to aflatoxin contamination through breeding has gained prominence because of: 1) the successful identification of germplasm resistant to aflatoxin contamination, and 2) the significant advances in the identification of natural resistance mechanisms and traits (Brown et al, 1999;Cleveland et al, 2003). However, these investigations indicated that resistance to aflatoxin contamination involves multiple chromosome regions and several genes .…”
Section: Prevention Of Contamination In Corn Through Enhancement Of Hmentioning
confidence: 99%
See 1 more Smart Citation
“…Le principal résultat publié sur l'arachide concerne une étude histologique de l'infection réalisée in situ grâce à un transformant de A. parasiticus utilisant comme promoteur un précurseur de l'aflatoxine, le gène Nor-1 [29]. Sur le maïs, des transformants A. flavus-GUS ont permis d'évaluer la croissance et le degré de l'infestation fongique [30] dans les graines et d'analyser l'expression des gènes reliés à l'aflatoxine [31].…”
Section: La Résistance à L'aflatoxine En Pré-récolteunclassified
“…The approach to enhance host resistance through conventional breeding and/or genetic engineering has gained renewed attention following the discovery of natural resistance to A. flavus infection and aflatoxin production in maize (Gardner et al, 1987;King and Scott, 1982;Widstrom et al, 1987;Scott and Zummo, 1988;White, 1995, Brown et al, 1995;Brown et al, 1999). Promising sources of resistant peanut germplasm have also been identified from a core germplasm collection, although resistance screening has proven to be a difficult task with this crop (Holbrook et al, 2008).…”
Section: Introductionmentioning
confidence: 99%